Wastewater infrastructure and the ecology and management of freshwater systems - Krista Arminty Capps (Acta Limnologica Brasiliensia)
Abstract Globally, freshwater resources are influenced by inputs of energy, nutrients, and pollutants from human wastewater. Local resource managers and policy-makers are tasked to address ecological and human-health concerns associated with aging and obsolete water infrastructure using limited financial resources. Nevertheless, there is limited information available describing how waste streams vary in their pollutant load or their subsequent effects on ecosystem structure and function in streams and rivers. Consequently, as wastewater systems degrade, local resource managers and policy makers are forced to develop watershed management strategies to deal with increasing effluent discharge without an understanding of how their decisions will influence local ecological processes or the structural and functional integrity of downstream habitats. Here, I discuss some of the ecological implications of obsolete or absent wastewater treatment, and describe how mismatches between the governance of wastewater management and watershed ecology may exacerbate environmental problems.